2021
DOI: 10.1155/2021/8847557
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cytokines as Potential Diagnostic Biomarkers for Systemic Lupus Erythematosus Disease

Abstract: Systemic lupus erythematosus (SLE) is a complex autoimmune inflammatory disease characterized by an unknown etiology and a highly variable clinical presentation. This clinical heterogeneity might be explained by dysregulation of tolerance to self and apoptotic mechanisms, overproduction of autoantibodies, and abnormal cytokine levels. Cytokine imbalance levels have been associated with disease activity and severity in SLE patients. In the last years, salivary cytokines related to SLE have gained significant at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to investigate the role of S100A8 protein as a diagnostic biomarker and its association with disease activity in patients with SLE using serum, urine, and saliva. It is important to analyze the S100 protein in the saliva of patients with SLE, which is a biofluid that is gradually receiving special attention, as it has been acknowledged that it contains many informative proteins about the disease process (44). Although the diagnostic ability of S100A8 that we have demonstrated is not superior to the diagnostic sensitivity and specificity of previously proposed classification criteria (45), it is worth emphasizing that we have discovered a powerful diagnostic biomarker in various biofluids.…”
Section: Discussionmentioning
confidence: 75%
“…To the best of our knowledge, this is the first study to investigate the role of S100A8 protein as a diagnostic biomarker and its association with disease activity in patients with SLE using serum, urine, and saliva. It is important to analyze the S100 protein in the saliva of patients with SLE, which is a biofluid that is gradually receiving special attention, as it has been acknowledged that it contains many informative proteins about the disease process (44). Although the diagnostic ability of S100A8 that we have demonstrated is not superior to the diagnostic sensitivity and specificity of previously proposed classification criteria (45), it is worth emphasizing that we have discovered a powerful diagnostic biomarker in various biofluids.…”
Section: Discussionmentioning
confidence: 75%
“…Some recent studies have focused on salivary inflammatory markers and they have found that salivary cytokines may be potential diagnostic biomarkers for SLE, where salivary IL-6 can be used to reliably assess the inflammatory process of SLE ( Stanescu et al, 2018 ; Zian et al, 2021 ).…”
Section: Manuscript Formattingmentioning
confidence: 99%
“…Researchers are attempting to objectively assess the body's response to a range of conditions, not only systemic, such as systemic lupus erythematosus (SLE), tuberculosis, or malignant processes [14,15], but also oral conditions, including periodontitis [16], caries [17,18], lichen planus [19], or peri-implantitis [20]. To this end, the levels of various cytokines, such as IL-1β, IL-2, IL-4, IL-5, IL-6, IL-7, IL-8, IL-10, IL-12, IFN-γ, TNF-α, and CRP, are monitored for diagnostic and prognostic purposes, and their fluctuations are reflected in the patient's clinical condition or to assess the severity of the disease [21,22].…”
Section: Introductionmentioning
confidence: 99%